1988
DOI: 10.1530/acta.0.1190181
|View full text |Cite
|
Sign up to set email alerts
|

3,3′,5′-Triiodothyronine inhibits ontogenetic development of iodothyronine-5′-deiodinase in the liver of the neonatal mouse

Abstract: To elucidate the effect of rT3 on iodothyronine-5\m='\-deiodinatingactivity (I-5\m='\-DA) in the liver of neonatal mice, rT3 was injected sc on the 5\p=n-\8thday after birth and I-5\m='\-DAin the liver was determined. A single injection of rT3 (0.01\p=n-\1\g=m\g/g) inhibited the ontogenetically developing I-5\m='\-DAin a dose-and ti me\x=req-\ dependent manner. The inhibitory effect was reversible and specific for I-5\m='\-DA.Lineweaver-Burk analysis revealed that the time-and dose-dependent decrease in the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…should be regarded with caution. The contamination of rT3 preparations from Calbiochem-Behring Corp. is rather unlikely since HAN et al (1988) were not able to detect any T3 and the level of T4 did not exceed 0.5 %.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…should be regarded with caution. The contamination of rT3 preparations from Calbiochem-Behring Corp. is rather unlikely since HAN et al (1988) were not able to detect any T3 and the level of T4 did not exceed 0.5 %.…”
Section: Discussionmentioning
confidence: 95%
“…Contrary to T3, rT3 decreases basal metabolic rate in mammals and fowl (LYNCH et al, 1985;VYBIRAL et al, 1985;ABDEL-FATTAH et al, 1990) and attenuates the hypermetabolic properties of T3 (ABDEL-FATTAH et al, 1990). Reverse TO also reduces the synthesis of T3 from T4 by reducing the activity of 5'-deiodinase type I and I1 (KAISER et al, 1986;HAN et al, 1988). CHOPRA (1977) has suggested that rT3 interacts with the binding sites of T3 in target cells.…”
Section: Introductionmentioning
confidence: 99%